Accessibility and Socio-economic Impact Assessment of Television in Rural Haryana - Preeti Singh and Seema Rani, (Indian Journal of Extension Education, 2014)
The study was conducted on a sample of 200 respondents comprising of 100 males and 100 females drawn from fourvillages of Hisar district. The data were collected on structured interview schedule on television. A majority of malerespondents had access to television, had complete control on use of television, had no control on selling and purchase oftelevision. Cent per cent of female respondents had no control on selling and purchase of television whereas a majority offemale (82.00%) respondents had complete control on use of television. As far as personal life of rural respondents isconcerned in case of male respondents television had increased awareness on current news and general awareness,provided entertainment, and changed fashion perception where as in case of personal life of female respondents televisionhad high impact in the areas of entertainment, current news/general awareness and decision making ability. Regardingsocial life of rural male respondents, television had high impact in areas of social awareness, awareness about domesticviolence and social messaging whereas in case of social life of female respondents television had high impact in areas ofsocial awareness, social status and level of social acceptance.Television had high impact on life of male and femalerespondents in the field of education which included career information, job opportunities and awareness aboutadmissions. As far as economic aspect is concerned television had positive impact on the aspects like market information,financial management and women's increased access to jobs. Regarding female respondents, television had higher impacton financial management, market information and personal and business contact. Impact of television on health andpolitical aspect reveals that television had high impact on awareness about diet/nutrition, meditation/yoga where as it hadmoderate impact on awareness about diseases. Regarding female respondent's television had high impact on awarenessabout diet/nutrition, moderate impact on awareness about diseases and awareness about medicines. Regardingagricultural aspect it was found that television had high impact on life of the male respondents in terms of improvement ofsales, information on crop production and preventing crop diseases whereas television had moderate impact onpreventing crop diseases, live stock keeping and animal fertility. Association of socio-economic variables of male andfemale respondents with access to television revealed that there was no significant association of age, education andoccupation on access to television. Association of socio-economic variables of male and female respondents for thosewho had control on television revealed that there was significant association of education with control of television.Significant association of complete access to impact of television, complete control on use of television & impact oftelevision and partial control on selling and purchase of television & impact of television was observed. Main constraintsin use of mobile were economic dependency, lack of decision making ability, lack of control on use of mobile and lack ofpower supply.